Acoustic measurements in eleven Italian opera houses: Correlations between room criteria and considerations on the local evolution of a typology. (December 2015) - Garai, M.; Morandi, F.; D'Orazio, D.; De Cesaris, S.; Loreti, L.
Abstract: Several studies focused on the acoustical characterisation of concert halls and opera houses analysing more or less homogeneous sets of halls and spotting reference criteria. This work presents the results of a detailed measurement campaign that was carried out over eleven small and mid-sized historical opera houses in the North of Italy with the aim of characterising this hall typology and to relate it to the reference literature. The cluster is intended to represent an adequate sample of case studies relative to different capacities and different design approaches that followed one another starting from the seventeenth century. The theatres were investigated using monaural and binaural techniques, performing impulse response measurements at each seat in the stalls and in each box. Seven ISO 3382 criteria are chosen to characterise these theatres and averaged over the three main listening areas denoted by the Italian opera house typology, i.e. the stalls, the boxes and the gallery. The correlation coefficients between interrelated criteria are presented and commented in relation to the architectural features of the theatres and to the existing literature. Highlights: The evolution of the Italian typology of mid and small-sized theatres is studied. A measurement campaign was carried out over 11 Italian historical opera houses. Over 50, 000 IRs were measured, leading to a detailed spatial characterisation. ISO 3382 criteria are analysed and related to the architectural features of the halls. Correlation coefficients between criteria are compared to the reference literature.